The Influence of Science Literacy-Based Teaching Material Towards Science Achievement - Avikasari Avikasari; Rukayah Rukayah; Mintasih Indriayu (International Journal of Evaluation and Research in Education (IJERE), 2018)
Based on PISA assessment result in 2015 on science; Indonesia ranks 69 out of 79 countries. Meanwhile, in science literacy, Indonesia ranks 62 out of 69 countries that are evaluated. That assessment result shows that science achievement and science literacy ability of Indonesian students are low. One of some factors that influences it is the selection of learning resource that does not explain science concept for students. This research is conducted to know the influence of the use of science literacy-based teaching material based on the improvement of fourth grade students’ science achievement. This research is a quantitative research that uses an experimental method. This research is conducted at two elementary schools in Gunungpati, Semarang. The subjects of this research are 46 fourth grade students. The data were collected by using pre-test and post-test to know the students’ score. This research shows that pre-test mean score is 39.935 and the post-test 1 mean score is 66.891. Meanwhile, t-tests show significance 0.000 (<0.05) meaning that there is the difference between pre-test and post-test. Therefore, there is influence on the use of science literacy-based teaching material based on fourth grade students’ science achievement.